People, politics, and pivots: sustaining research-practice partnership collaboration - Weddle, Hayley; Hopkins, Megan; Shanahan, Katie; Stern, Sierra (Frontiers in Education, 2025)
A growing body of scholarship outlines the value of research-practice partnerships (RPPs) for disrupting inequities across education systems. While promising, RPP work is also complex as partners navigate politics, turnover, and distinct organizational cultures and goals. To support the field with navigating such complexities, we examine approaches for sustaining RPP collaboration over time. Our work is situated in a national RPP that brings together researchers and 30 leaders across 28 state education agencies to improve multilingual learner policy and practice. Analysis of extensive interview and observation data collected over five years revealed practices supporting joint work amidst significant shifts in membership and national politics. We conclude with actionable recommendations for researchers and practitioners to sustain RPP collaboration over time.